Visualization of IOL Material-Induced Changes in Retinal Color Stimulus - Stephan Reiss; Karsten Sperlich; Martin Kunert; Rudolf F. Guthoff; Heinrich Stolz; Anselm Jünemann; Oliver Stachs (Journal of Ophthalmology)
Purpose. Different IOL materials, particularly blue-light filtering materials, have different spectral transmittance characteristics. The color stimuli, which influence retinal receptors objectively, have consequently implications for color perception. We report on the quantitative determination of IOL-specific transmittance characteristics and present a method visualizing the resultant changes in color stimulus. Methods. A setup was realized to quantify IOL-absorption in a range of 390–780 nm. To visualize the influence of the different spectral transmittance characteristics an algorithm was developed, which converts RGB-pixel values of images into spectra, which performs the corresponding transmittance correction, reconverts to RGB, and reconstructs the image. IOLs of hydrophobic acrylate and hydrophilic acrylate with a hydrophobic surface in each case with/without blue-light filter were examined. Results. Assessment of the reference images verifies the suitability of the pipeline. Evaluation of the transmittance spectra reveals differences of material- and manufacturer-specifics, which are capable of inducing considerable changes in color perception, particularly in the blue color range and mixed colors involving blue. Conclusions. The developed technique provides an approach for determining IOL-specific transmittance behavior and subsequently its influence on the retinal color stimulus. Problems of altered color perception are occasionally reported after cataract surgery and these become obvious with the visualization procedure developed here.